BUKIT CINTA CAMPUHAN SEBAGAI DAYA TARIK WISATA TREKKING DI UBUD BALI - Kawakibi Pritiwasa, I Wayan Thariqy; Demolingo, Ramang Husin (Jurnal Analisis Pariwisata; Vol 20 No 01 (2020): Jurnal Analisis Pariwisata (2020), 2021)
The instrument in this study was tourists visiting the region in 2019, the results of the study showed that the attraction of climbing tourism was able to increase the potential of nature to be preferred for tourists, improve the economy of the local community, encourage reconnaissance of the environment, and nature and culture. an interesting form of activity that has a concern for environmental sustainability. The attraction of trekking in the hills love of Campuhan Ubud will offer the concept of natural tourism that adds to the beauty, uniqueness, rarity, and tourist activities related to trekking activities. Keywords: Trekking activity, tourism, tourists, community, environment